Pengaruh Relaksasi Otot Progresif terhadap Kualitas Tidur pada Lansia - Lucia Arum Sari; Dinasti Pudang Binoriang (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Old age is the final phase in the human life cycle, characterised by a decline in physiological function. Global data shows that the prevalence of old age will increase from 33.69 million to 48.19 million by 2035. One of the effects of this decline in physiological function is a disruption in the quality of sleep among the elderly. As many as 50-60% of elderly people in Indonesia experience sleep disorders. One way to overcome sleep disorders is through relaxation therapy. Progressive Muscle Relaxation is a technique performed by stretching and relaxing certain muscles to relax the body. The purpose of this study was to determine the effectiveness of progressive muscle relaxation on the quality of sleep in elderly people. This research method involved a nursing care process from assessment to evaluation using a case study design. The research sample consisted of one elderly person with moderate sleep quality. The intervention was given for 10-15 minutes using eight movements with a frequency of twice a week for one month. The data were analysed using pre-test and post-test PSQI questionnaires to determine sleep quality. The results of this study indicate that progressive muscle relaxation training has an effect on improving sleep quality in the elderly.